Going the (Ethical) Distance - Shepski, Lee (2013)
Nearly every day we participate in the vast, interconnected global economy. In doing so, we engage in chains of transactions that ultimately result in our benefiting from, or enabling, wrongdoing by others. In some cases this seems to be in itself wrong, but in many cases it seems unproblematic. I develop a concept of ‘ethical distance’ and argue that our responsibility for the wrongdoing of others is a function of our ethical distance from it. Furthermore, I argue that the concept of moral responsibility is vague, but that when we become clearly responsible for wrongdoing by others, we ought to sever our connection to it.
Keywords: Vague predicates; Transaction partners; Moral Responsibility; ethical distance